Expression of c-FLIPL and resistance to CD95-mediated apoptosis of monocyte-derived dendritic cells: inhibition by bisindolylmaleimide - Willems, Fabienne; Peter, Marcus E.; Krammer, Peter H. (Blood, 2000)
To gain insight into the mechanisms controlling apoptosis of dendritic cells (DC), human monocyte-derived DC were analyzed for their expression of CD95 (Fas/Apo-1) and their response to CD95 ligation. Although DC expressed the CD95 molecule on their membrane, they did not undergo apoptosis on CD95 ligation unless sensitized by cycloheximide. In parallel, DC synthesized c-FLIPL, an inhibitor of the CD95-mediated death-signaling cascade. We also demonstrated that bisindolylmaleimide down-regulates c-FLIPL expression in DC and, in parallel, allows CD95-mediated apoptosis in these cells. In contrast, Bcl-2, Bcl-xl, and Bax levels were not affected by bisindolylmaleimide. We conclude that DC resist CD95- mediated apoptosis in association with c-FLIPLexpression and that the immunosuppressive potential of bisindolylmaleimide previously observed at the T-cell level also involves facilitation of CD95-mediated DC apoptosis.
Gesehen am 27.04.2021
Im Titel ist der Buchstabe "L" im Ausdruck "c-FLIPL" tiefgestellt